Enhanced EMW absorption properties of SiCN/Fe/Ni ceramics modified with Fe/Ni bimetal. Issue 20 (15th October 2022) - Liu, Jie; Liu, Chunmiao; Tong, Yanchun; Sun, Haibin; Peng, Hui; Zhang, Mingwei; Wu, Shigang; Zhang, Hongying; Gong, Hongyu; Zheng, Zhiqin; Guo, Xue; Feng, Yurun
Abstract: The SiCN/Fe/Ni ceramics codoped with iron acetylacetonate (FA) and nickle acetylacetonate (NA) was synthesized by polymer-derived ceramics (PDCs) method in this study. The microstructure, phase composition and electromagnetic wave (EMW) absorption properties of the samples were analyzed. The polarization loss and conduction loss of materials were analyzed by the direct current (DC) multimeter and the contribution rate of polarization loss was more than 94% in the whole frequency band. The results showed that C, SiC, Fe2 Si, Ni3 Si, γ- (Fe, Ni) and CNTs were formed after pyrolysis which provided lots of heterogeneous interface and enhanced the interfacial polarization. Meanwhile, Ni could enter the lattice of Fe and formed a unique electronic configuration, which reinforced the conductivity and stability of Fe. In addition, the in-situ generated Fe2 Si and Ni3 Si provided magnetic loss and conduction loss. The RLmin value of SiCN/Fe/Ni-3 ceramic was −52.06 dB at 1.54 mm and the effective absorption band (EAB, RL ≤ −10 dB) reached 4.21 GHz (13.79–18 GHz, 1.43 mm). Graphical abstract: Image 1